Formulation Development and Optimization of Immediate Release Layer for Bilayer Gastroretentive Tablet of Nizatidine Using 32 Factorial Design Model - Garg, Rahul Kumar; Indrajeet, Singhvi (Asian Journal of Pharmaceutical Research and Development, 2015)
The main objective of this study is to prepare and optimized the formula of Immediate Release layer for bilayer gastro retentive floating tablet of Nizatidine using 32 Factorial Design. Nizatidine having biological half life (1 to 2 hours), selected model drug as it is Competitive inhibition of histamine at H2 -receptors of the gastric parietal cells resulting in reduced gastric acid secretion, gastric volume and hydrogen ion concentration in the upper part of GIT hence it is suitable for gastro retentive system. In this study Immediate Release layer was prepared by superdisintegrant sodium starch glycolate, Crosspovidone and microcrystalline cellulose. The IR layer was characterized by initially Flow Property of blend and further characterized for Hardness, Friability, Disintegration time and drug content. Finalized the formula for IR layer on the basis of Friability and Disintegration time data study with design expert software 32 Model. Validation of Model has confirmed using linear correlation plots and residual plots.